2019
DOI: 10.1186/s13065-019-0529-3
|View full text |Cite
|
Sign up to set email alerts
|

On the role of composition and processing parameters on the microstructure evolution of Ti-xMo alloys

Abstract: Laser Engineered Net Shaping (LENS™) was used to produce a compositionally graded Ti-xMo (0 ≤ x ≤ 12 wt %) specimen and nine Ti-15Mo (fixed composition) specimens at different energy densities to understand the composition–processing–microstructure relationships operating using additive manufacturing. The gradient was used to evaluate the effect of composition on the prior-beta grain size. The specimens deposited using different energy densities were used to assess the processing parameters influence the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…[ 143–145 ] Then the electron probe microanalysis (EPMA), X‐ray fluorescence, X‐ray diffraction, nanoindentation, and other techniques would be used to measure and obtain local compositions, crystal structures, and/or properties (e.g., hardness, elastic modulus, electrical conductivity, thermal expansion coefficients, and so on). This approach has been used in the design of many kinds of materials such as high‐entropy alloys, [ 146–149 ] bulk metallic glasses, [ 145,150–152 ] and Ti alloys [ 153–155 ] including those with a low elastic modulus. Teixeira et al [ 156 ] used a laser to deposit the pure Ti and pure Ta powders on a substrate to develop Ti–Ta alloys for biomedical applications.…”
Section: Design Methods For Low‐modulus Ti Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 143–145 ] Then the electron probe microanalysis (EPMA), X‐ray fluorescence, X‐ray diffraction, nanoindentation, and other techniques would be used to measure and obtain local compositions, crystal structures, and/or properties (e.g., hardness, elastic modulus, electrical conductivity, thermal expansion coefficients, and so on). This approach has been used in the design of many kinds of materials such as high‐entropy alloys, [ 146–149 ] bulk metallic glasses, [ 145,150–152 ] and Ti alloys [ 153–155 ] including those with a low elastic modulus. Teixeira et al [ 156 ] used a laser to deposit the pure Ti and pure Ta powders on a substrate to develop Ti–Ta alloys for biomedical applications.…”
Section: Design Methods For Low‐modulus Ti Alloysmentioning
confidence: 99%
“…electrical conductivity, thermal expansion coefficients, and so on). This approach has been used in the design of many kinds of materials such as high-entropy alloys, [146][147][148][149] bulk metallic glasses, [145,[150][151][152] and Ti alloys [153][154][155] including those with a low elastic modulus. Teixeira et al [156] used a laser to deposit the pure Ti and pure Ta powders on a substrate to develop Ti-Ta alloys for biomedical applications.…”
Section: High-throughput Experimentsmentioning
confidence: 99%
“…The microstructure is defined by heat transfer, fluid dynamics, phase transformations and the thermophysical properties of the material. Knowing the microstructure evolution in AM is very important to determine the properties of the material (Mendoza et al [2019]). AM is a process that involves a condition that is far from thermodynamical equilibrium due to the rapid solidification.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…Alloying elements such as boron (B) (Bermingham et al [2008]) and beryllium (Be) (Bermingham et al [2009]) acting as good grain refiners. All these efforts were focused on casting titanium alloys, but the fundamentals were extrapolated to additive manufacturing on titanium alloys for alloying elements such as molybdenum (Mo) (Mendoza et al [2019]) and tungsten (W) ). More recent research revealed the grain refiner power of lanthanum oxide (La 2 O 3 ) (Ng et al [2022]) and an hydrogenation treatment on wire arc additive manufacturing (WAAM) (Xiaolong et al [2022]).…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…Here the research in DED-processed FGMs also helps to establish the process-structure-property relationship of these promising alloy systems. Ti-Cr [68], Ti-Al [69], Ti-W [70], and Ti-Mo [71] systems were also investigated. Details are tabulated in Table 1.…”
Section: Fgmsmentioning
confidence: 99%